ANALISIS KINERJA WAKTU DENGAN MENGGUNAKAN PRECEDENCE DIAGRAM METHOD (PDM) (Reschedule Proyek Pembangunan Jembatan Nangarasong, Kabupaten Sikka, Nusa Tenggara Timur) - Claudia Ekarista Sika Keytimu; Oktavianus Jori (Program Studi Teknik Sipil, 2022)
Construction projects are developing rapidly both in terms of physicality, time and cost, this rapid construction development is certainly also felt by the construction of the bridge. In the construction of bridges, it often faces challenges in terms of incompatibility between planning schedules and realization in the field. The bridge project that will be used as a case study is located in the Nangarasong area, Sikka Regency, East Nusa Tenggara. This study uses the Precedence Diagram Method (PDM) which aims to find out the time comparison and evaluate the solution of the project implementation time. The method was analyzed using Microsoft Excel and three scenarios were obtained for the duration of the project implementation, namely: the realization time obtained a duration of 126 calendar days, the time according to the number of workers at the location obtained a duration of 120 calendar days, and the time with the number of workers obtained a duration of 112 calendar days. Thus, the project implementation time was accelerated by 12 calendar days.